PENGARUH KEAMANAN TRANSAKSI KEPERCAYAAN KONSUMEN DAN GAMIFIKASI TERHADAP LOYALITAS PELANGGAN PADA MARKETPLACE SHOPEE - Wana Hidayah; Tengku Syarifah (Smart Education, 2026)
This study aims to determine the simultaneous and partial effects of transaction security, consumer trust, and gamification on customer loyalty in the Shopee marketplace. This research employed a quantitative descriptive approach. The data analysis technique used was multiple linear regression. The sample was determined using a non-probability sampling technique through the Cochran approach, resulting in a total of 100 respondents. Validity and reliability tests were also conducted on the respondents as the research sample. The results of the multiple linear regression analysis produced the following equation: Y = 20.043 + 0.582X₁ + 0.488X₂ + 0.110X₃. The results of the F-test indicate that H₁ is accepted and H₀ is rejected, meaning that transaction security, consumer trust, and gamification simultaneously have a significant effect on customer loyalty, with an Fcount value of 18.708 which is greater than the Ftable value of 2.70. The results of the t-test indicate that H₂ is accepted and H₀ is rejected, meaning that transaction security partially has a significant effect on customer loyalty with a tcount value of 3.857 which is greater than the ttable value of 1.985. Consumer trust also has a significant effect on customer loyalty with a tcount value of 4.741 which is greater than the ttable value of 1.985. Furthermore, gamification has a significant effect on customer loyalty with a tcount value of 6.937 which is greater than the ttable value of 1.985. Based on the tcount values, the gamification variable is the most dominant factor influencing customer loyalty. The results of the coefficient of determination test (R²) show that the adjusted R square value is 0.409, indicating that transaction security, consumer trust, and gamification explain 40.9% of the variation in customer loyalty, while the remaining 59.1% is influenced by other factors not included in this study.